Insurance Class Actions in the United States - Pace, Nicholas M. (RAND Corporation, 2007)
Class actions, which are civil cases in which parties initiate a lawsuit on behalf of other plaintiffs not specifically named in the complaint, often make headlines and arouse policy debates. However, policymakers and the public know little about most class actions. This book presents the results of surveys of insurers and of state departments of insurance to learn more about class litigation against insurance companies.